Ophthalmic patterns of captive brown brocket deer (Mazama gouazoubira) - Martins, Bianca C. [UNESP]; Oriá, Arianne P. [UNESP]; Souza, Ana L. G. [UNESP]; Campos, Carla F. [UNESP]; Almeida, Denise E. [UNESP]; Duarte, Roberta A. [UNESP]; Soares, Christiane P. [UNESP]; Zuanon, José A. S. [UNESP]; Neto, Carlos B. [UNESP]; Duarte, José M. B. [UNESP]; Schocken-Iturrino, Rubén P. [UNESP]; Laus, José L. [UNESP] (American Association of Zoo Veterinarians, 2007)
Captive brown brocket deer (Mazama gouazoubira) were manually restrained to assess tear production by the Schirmer tear test I to measure intraocular pressure by applanation tonometry, to examine ocular conjunctival epithelial cells via cytologic and histologic samples, and to survey ocular conjunctival microflora by microbiologic culture. The mean value for the Schirmer tear test I was 8.9 ± 1.8 mm/min, and the mean intraocular pressure was 15.3 ± 3.1 mm Hg. Conjunctival epithelium contained stratified pavimentous layers of cells, and the microflora consisted of predominantly gram-positive bacteria. Copyright 2007 by American Association of Zoo Veterinarians.
Keywords: Brown brocket deer; Conjunctival microflora; Eye; Intraocular pressure; Mazama gouazoubira; Tear production; animal; animal disease; conjunctiva; cytology; deer; female; intraocular pressure; lacrimal fluid; male; microbiology; oculoplethysmography; physiology; reference value; secretion; zoo animal; Animals; Animals, Zoo; Conjunctiva; Deer; Female; Intraocular Pressure; Male; Reference Values; Tears; Tonometry, Ocular; Cervidae; Mazama gouazoupira; Posibacteria